Intestinal microbiota in adults with cholangiocarcinoma identifies the dysregulated Blautia species and bile acid metabolic pathways - Tianyu De; Tian Ma; Wei Wang; Xusheng An; Di Liu; Hongkun Yin; Qi Wang; Ting Zhao; Hao Wang (BMC Gastroenterology)
Abstract Background Cholangiocarcinoma (CCA) represents a significant global health concern. The gut and bile microbiota, which can influence the gut-liver axis and disease progression, have not been thoroughly characterized in CCA patients. Methods We selected two clinical centers at our hospital and collected stool samples from CCA patients and healthy controls (HC). These samples underwent whole-genome metagenomic shotgun sequencing, followed by analysis using both marker gene-based and assembly-based methods. Additionally, KEGG pathway enrichment was performed using the cholangiocarcinoma (CHOL) RNA-seq samples. Results Our results revealed distinct dysbiosis of the gut microbiota in our regional CCA patients. The results revealed greater heterogeneity in the gut microbiome of CCA patients compared to HC samples. We found Blautia species to be significantly less abundant in CCA samples, and can distinguish CCA patients from HC. Blautia can also play a role in influencing the modification of secondary bile acids. Additionally, down-regulation of arachidonic acid and linoleic acid metabolism was observed in the tumor tissues of CHOL patients. In summary, the results revealed significant heterogeneity difference in the gut microbiome of CCA patients compared to HC samples, and detected the specifically decreased Blautia species in CCA patients, suggesting that Blautia may influence bile acid metabolic pathways. Further investigation is warranted to explore Blautia as a potential biomarker for CCA.